Method‐of‐use study of naltrexone sustained release (SR)/bupropion SR on body weight in individuals with obesity. Issue 2 (27th December 2016) - Halseth, Amy; Shan, Kevin; Walsh, Brandon; Gilder, Kye; Fujioka, Ken
Abstract : Objective: This study assessed the effects of 32 mg naltrexone sustained release (SR)/360 mg bupropion SR (NB) on body weight in adults with obesity, with comprehensive lifestyle intervention (CLI), for 78 weeks. Methods: In this phase 3b, randomized, open‐label, controlled study, subjects received NB + CLI or usual care (standard diet/exercise advice) for 26 weeks. NB subjects not achieving 5% weight loss at week 16 were discontinued, as indicated by product labeling. After week 26, usual care subjects began NB + CLI. Assessments continued through week 78. The primary end point was percent change in weight from baseline to week 26 in the per protocol population. Other end points included percentage of subjects achieving ≥5%, ≥10%, and ≥15% weight loss, percent change in weight at week 78, and adverse events (AEs) necessitating study medication discontinuation. Results: NB + CLI subjects lost significantly more weight than usual care subjects at week 26 (8.52% difference; P < 0.0001). Weight loss persisted through 78 weeks. In total, 20.7% of subjects discontinued medication for AEs, including 7.0% for nausea. Conclusions: Treatment with NB, used as indicated by prescribing information and with CLI, significantly improved weight loss over usual care alone. NB‐facilitated weight loss was sustained for 78 weeks and was deemed safe and well tolerated.